2006
DOI: 10.1016/j.jtcvs.2005.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Is surgical resection indicated for a solitary non–small cell lung cancer recurrence?

Abstract: Resection of a solitary non-small cell lung cancer recurrence might provide long-term survival in highly selected patients. However, surgical resection might be contraindicated if the primary tumor is stage II or III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…However some investigators showed long-term survival after operative treatments in selected patients; Hishida et al reported a satisfactory outcome after resection of lung cancer recurrence in stage I patients. 18 Aokage et al observed prolonged survival after surgery in two patients with diagnosis of solitary gastric metastasis from pulmonary pleomorphic carcinoma. 19 Moreover surgical treatment of such recurrences may be indicated if bleeding or obstruction is encountered.…”
Section: Discussionmentioning
confidence: 98%
“…However some investigators showed long-term survival after operative treatments in selected patients; Hishida et al reported a satisfactory outcome after resection of lung cancer recurrence in stage I patients. 18 Aokage et al observed prolonged survival after surgery in two patients with diagnosis of solitary gastric metastasis from pulmonary pleomorphic carcinoma. 19 Moreover surgical treatment of such recurrences may be indicated if bleeding or obstruction is encountered.…”
Section: Discussionmentioning
confidence: 98%
“…When possible, surgical resection is reported to be the best approach [18]. Other authors would only consider reintervention when the primary tumour was determined to be stage I disease [74].…”
Section: Distant Metastasesmentioning
confidence: 99%
“…Such limited metastases are referred to as oligometastases. Local therapy, such as surgery and radiotherapy, has been applied successfully in appropriately selected patients, especially for patients with either brain metastasis alone or those with adrenal metastasis alone [31][32][33][34] . Recently, Yano et al reported a retrospective study reviewing their therapeutic experience with postoperatively recurrent NSCLC patients and demonstrated that a histology of adenocarcinoma, a longer disease-free interval (≥ 1 year) and the use of local therapy are significantly preferable prognostic factors for the postrecurrence OS of patients with distant metastasis alone [6] .…”
Section: Treatment Of Oligometastatic Recurrencementioning
confidence: 99%